Maternal fiber deprivation alters microbiota in offspring, resulting in low-grade inflammation and predisposition to obesity - Zou, Jun; Ngo, Vu L.; Wang, Yanling; Wang, Yadong; Gewirtz, Andrew T. (Cell host & microbe, 2023)
Diet, especially fiber content, plays an important role in sustaining a healthy gut microbiota, which promotes intestinal and metabolic health. Another major determinant of microbiota composition is the specific microbes that are acquired early in life, especially maternally. Consequently, we hypothesized that alterations in maternal diet during lactation might lastingly impact the microbiota composition and health status of offspring. Accordingly, we observed that feeding lactating dams low-fiber diets resulted in offspring with lasting microbiota dysbiosis, including reduced taxonomic diversity and increased abundance of Proteobacteria species, despite the offspring consuming a fiber-rich diet. Such microbiota dysbiosis was associated with increased encroachment of bacteria into inner mucus layers, low-grade gut inflammation, and a dramatically exacerbated microbiota-dependent increase in adiposity following exposure to an obesogenic diet. Thus, maternal diet is a critical long-lasting determinant of offspring microbiota composition, impacting gut health and proneness to obesity and its associated disorders. [Display omitted] •Maternal fiber deprivation lastingly and detrimentally influenced microbiome of offspring•Maternal fiber deprivation resulted in low-grade gut inflammation in offspring•Offspring of fiber-deprived mice were highly prone to develop obesity•Enriching maternal diet with fiber restored microbiome of offspring and prevented obesity Zou et al. show that consumption of low-fiber diets by lactating mice caused offspring to exhibit lasting microbiota dysbiosis and a propensity for obesity despite the offspring consuming fiber-rich diets. These findings indicate that dietary fiber consumption by lactating mothers critically determines the intestinal and metabolic health of offspring.